(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article delves into the unique linguistic features of the language used on Instagram, one of the most popular social media platforms. Through a comprehensive analysis, it aims to uncover the distinct elements that characterize communication within this digital space. By employing methods from discourse analysis and internet linguistics, we explore how Instagram users express themselves, connect, and engage through language. The findings contribute to a better understanding of the evolving nature of communication in the digital age.